GEOINFORMATION SYSTEM FOR THE ANALYSIS AND VISUALIZATION OF GEOSPATIAL DATA IN THE REGIONS OF WESTERN KAZAKHSTAN - Buribaev, Ж.А.; Abdirazak, З.Б.; Yerkos, А.; Zhassuzak, М.С.; Omarova, П.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The research is devoted to the development of a geoinformation portal for a comprehensive analysis of the environmental, economic and social situation in Western Kazakhstan. The aim of the work was to create a tool to assess the impact of climate change on the state of water resources and biodiversity in the region. Meteorological data, soil data and socio-economic indicators were used as input data. The developed portal allows for spatial and temporal data analysis, visualization of results in the form of maps, graphs and diagrams. The system is based on Python/Django, PostgreSQL and OpenStreetMap technologies. The portal provides an opportunity to assess the dynamics of vegetation cover changes, analyze the relationship between climatic factors and the state of ecosystems. The developed tool can be used to make informed decisions in the field of environmental management and environmental protection in Western Kazakhstan.